Delivering a disease-modifying treatment for Huntington’s disease - Godinho, Bruno M. C. (2014)
Huntington's disease (HD) is an incurable genetic neurodegenerative disorder that leads to motor and cognitive decline. It is caused by an expanded polyglutamine tract within the Huntingtin (HTT) gene, which translates into a toxic mutant HTT protein. Although no cure has yet been discovered, novel therapeutic strategies, such as RNA interference (RNAi), antisense oligonucleotides (ASO), ribozymes, DNA enzymes, and genome-editing approaches, aimed at silencing or repairing the mutant HTT gene hold great promise. Indeed, several preclinical studies have demonstrated the utility of such strategies to improve HD neuropathology and symptoms. In this review, we critically summarise the main advances and limitations of each gene-silencing technology as an effective therapeutic tool for the treatment of HD.